Mondreng Traditional Art as a Cultural Learning Resource in Local Wisdom-Based Art Education - Sarjoko, Moh; Sunarto, Sunarto; Suharto, Suharto; Djatiprambudi, Djuli (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze Mondreng traditional art as a cultural learning resource in local wisdom-based art education. The research was conducted in Dayu Village, Nglegok District, Blitar Regency, East Java, Indonesia, where Mondreng art is actively practiced within the community. This study employed a qualitative descriptive approach to explore the cultural meanings and educational potential of Mondreng art. Data were collected through in-depth interviews, observations, and documentation involving seven informants consisting of Mondreng performers, art group leaders, cultural figures, art teachers, school principals, local cultural office representatives, and youth participants. Data were analyzed using qualitative data analysis techniques involving data reduction, data presentation, and verification. The findings reveal that Mondreng art has a structured performance consisting of musical elements, shalawat poetry, and collective performance practices that reflect social, cultural, and spiritual values. Mondreng is not only performed as a form of entertainment but also functions as a medium for cultural transmission through community-based practices. The involvement of the community plays a crucial role in maintaining its sustainability and ensuring intergenerational knowledge transfer. Furthermore, Mondreng art demonstrates strong potential as a contextual learning resource in art education. Its integration into learning enables students to understand artistic practices in relation to their cultural environment while fostering values such as cooperation, religious awareness, and cultural appreciation. This study contributes to the development of ethnopedagogy by positioning local traditional art as a meaningful and relevant source of learning in contemporary education.